"LOKALLIK” IN UZBEK LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article stressed about the concept of integrity and space of the Uzbek language, which consists of interrelated, interdependent elements. The semantic field is also a structure, like other systems.